2010
DOI: 10.1177/0333102410382794
|View full text |Cite
|
Sign up to set email alerts
|

One-year prevalence of migraine in Spain: A nationwide population-based survey

Abstract: The one-year prevalence of migraine in Spain is 12.6%, with a prevalence of migraine with and without aura of 8.4% and probable migraine of 4.2%. These findings add data to the current understanding of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 39 publications
4
45
2
9
Order By: Relevance
“…In Fallahzadeh et al study, 26.5% of migraineurs and 4% of patients with TTH did not refer to the doctor for treatment of their headaches [26]. Also, in a study conducted in Spain found that one third of migraineurs did not refer to the doctor for diagnosis of migraine [10]. Design of present study in form of cross-sectional and self-reporting was limiting factor.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In Fallahzadeh et al study, 26.5% of migraineurs and 4% of patients with TTH did not refer to the doctor for treatment of their headaches [26]. Also, in a study conducted in Spain found that one third of migraineurs did not refer to the doctor for diagnosis of migraine [10]. Design of present study in form of cross-sectional and self-reporting was limiting factor.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies have estimated the prevalence of migraine and TTH based on the criteria of the IHS. The prevalence of migraine have been reported in studies done in Iran and different countries such as Germany (10.6%), Spain (12.6%), and Brazil (22.1%); hospital staff of Shiraz in Iran (11.2%) [9][10][11][12]. Also, the prevalence of TTH reported in other studies such as Brazil (22.9%) and hospital staff (19.5%), teachers (24%) and students of Shiraz (32%) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 95%
“…With this in mind, researchers conducting community studies have debated the use of different strategies, whether face-to-face, mail based, or web based [1]. Potential methods for collecting specific information [2] range from door-to-door studies, used in research on low-prevalence diseases, to those conducted using traditional mail, telephone [3], the Internet [4, 5], interactive voice response (IVR) [6, 7], computer-assisted telephone interview (CATI) [8, 9], or combinations of the above methods [1013]. In any case, the method delivering the highest RR would be considered the most efficient and appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…The Ferrante et al (2012) study reports a prevalence of 0.2% (0.0% for men and 0.4% for women) for (ICHD-2) chronic migraine, possibly on the low side compared to earlier studies using these restrictive criteria (6,21). The definition and hence epidemiology of very frequent headache/chronic migraine has of course evolved over the last 20 years or so.…”
mentioning
confidence: 99%
“…Might the prevalence of migraine in Italy vary by geographical region? For example, a nationwide, population-based study of migraine in Spain showed an overall migraine prevalence of 12.6% but significant geographical variation (> twofold) was reported, from 7.6% in Navarra to 18% in the Canary Islands (6).…”
mentioning
confidence: 99%